(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
He sociocultural anthropology of the community of El Realejo, municipality of the Department of Chinandega is a topic of great importance that needs to be analyzed; it is a population located on the archeohistorical vestiges of what was the first geographical colonial space of Nicaragua. The conqueror Andrés Niño baptized it as Port of Possession in 1522 and formally annexed it to the properties of the Spanish Crown, as part of the Western invading policies, years later it was called Puerto de la Posesión de El Realejo by the foundation of La Villa de El Realejo in 1534 and hence derives its current name. For a little over three hundred years it was one of the most important colonial ports in Central America. In 2005, we carried out anthropological, archaeological and historical studies in the current population; obtaining interesting data about the colonial location, the living community and the relationship between both through its Material and Intangible Cultural Heritage. The wealth of the municipality can be exploited for the development of Sustainable Community Tourism that would improve the local economy while protecting, preserving, disseminating and achieving the value of this Cultural Heritage of the Nation Municipality.